Cases of bat deaths associated with plants - Merzlikin, I. (Праці теріологічної школи, 2017)
Presented here are the accidents that happened with bats on plants having thorns (Prunus spinosa, Robinia pseudoacacia), spines (Arctium sp., Ancistrocactus megarhizus), and sticky buds (Aesculus hippocastanum). Bats clung on thorns and spines of plants by their wings, and stuck to sticky buds of horse chestnut and could not get rid of. Bats have begun to face new problems for themselves related to the elements introduced by man into their habitat (including cacti) or unnatural shelters (buildings). Подано опис нещасних випадків, які трапилися з кажанами на рослинах, які мають колючки (Prunus spinosa, Robinia pseudoacacia), гачки (Arctium sp., Ancistrocactus megarhizus) та липкі бруньки (Aesculus hippocastanum). Кажани чіплялися перетинками на крилах за голки та гачки рослин та приклеїлися до липких бруньок каштану гіркого і не могли звільнитися. Кажани почали зустрічатися з новими для себе проблемами, які пов'язані з елементами, привнесеними людиною в їх середовище проживання (зокрема й кактусами) або у місця неприродних сховищ (людські будівлі).